Planar defects in photonic crystals - V. Karathanos; A. Modinos; N. Stefanou (Journal of Physics: Condensed Matter, 1994)
We establish the existence of an absolute frequency gap of the electromagnetic field in photonic crystals with tetragonal symmetry, and examine the dependence of the gap on the geometry of the structure. We calculate the transmittance through a slab of finite thickness of the material, and show that planar defects in the slab produce interface states of the electromagnetic field, at frequencies within the photonic gap, manifested by sharp resonances in the transmittance of these systems.